Penerapan Akuntasi Berdasarkan SAK ETAP pada DIY (Do It Yourself) UMKM di Kabupaten Lumajang - Rizal Tri Arifiyanto; Gaguk Apriyanto; Maxion Sumtaky (University of Merdeka Malang, 2021)
This study aims to analyze the application of accounting in DIY (Do It Yourself) MSME in Lumajang Regency and analyze the suitability of accounting application in the DIY (Do It Yourself) MSME in Lumajang Regency with SAK-ETAP. Researchers used qualitative descriptive research methods. The sample in this study was 10 respondents, the sampling technique used was the census. The analysis technique is through data collection, data reduction, data presentation and conclusion drawing. The application of accounting DIY (Do It Yourself) MSME in Lumajang Regency is still very simple, most of them only record income and expenses and are recorded manually. The application of accounting in DIY (Do It Yourself) MSME in Lumajang Regency has not yet been in accordance with Financial Accounting Standards Without Public Accountability, because there are several stages that have not fulfilled the accounting cycle. This is due to a lack of technical knowledge in the preparation of financial reports, especially based on SAK-ETAP and a lack of awareness from the DIY (Do It Yourself) in Lumajang Regency about the importance of complete and standardized financial reports. The DIY MSME in Lumajang Regency feels that the financial statements that show the company's profit and loss are sufficient.